Oral Infections and Systemic diseases - Prof. Dr. S. Akhtar Hussain Bokhari (Journal of University Medical & Dental College, 2020)
Oral health is part of systemic health, however medical and dental clinicians treat the oral cavity as if it is a separate entity from the rest of the body. An interrelationship between oral health and systemic health exists but causality is yet to be understood and proven.